School boundaries coming alive: Transforming education towards sustainability through open schooling initiatives - Erik Knain; Giulia Tasquier; Alfredo Jornet; Hanna Rokenes; Martin Lee Mueller (Acta Psychologica, 2025)
Open schooling initiatives challenge traditional boundaries of how, where, involving whom, and for what purpose education takes place. Here, we map some core challenges and potentials of open schooling as a means to expand schools' traditional institutional boundaries. Specifically, we critically reflect on three interrelated dimensions of boundary expansion in the context of open schooling: 1) Expanding the notion of discipline, knowledge and knowing (The Disciplinary Dimension); 2) Expanding collaboration and collective agency (The Social-Relational Dimension); and 3) Regenerating the schooling (eco)system (the inter-institutional dimension). We argue that navigating such boundary expansions judiciously is crucial as researchers in education ask how to realign education with the larger, ongoing societal transformation that is required to move towards more socially just and sustainable societies. We lean into the ‘three spheres of transformation’ model to analyse how to keep boundaries alive in their dual contradictory but crucial meaning and role to separate and connect, at the same time, across the various dimensions of transformation.